Determinants of Two-Wheeled Motor Vehicle Taxpayer Compliance at UPPD Samsat Banjarmasin - Nabilla Rizqa Mustafa; Saifhul Anuar Syahdan; Gemi Ruwanti; Soelistijono Boedi (Politeknik Ganesha Medan, 2026)
This study investigates the factors determining motor vehicle tax compliance among owners of two-wheeled vehicles in Banjarmasin, Indonesia, by evaluating both the combined and individual contributions of fiscal policy incentives and behavioral factors. Consistently low compliance rates among registered vehicle owners continue to hinder local tax revenues, highlighting the urgency of identifying the reasons influencing compliance behavior. This study aims to analyze the simultaneous and partial effects of the tax amnesty program, transfer fee exemptions, taxpayer awareness, tax understanding, and service quality on taxpayer compliance at UPPD Samsat Banjarmasin I. Utilizing quantitative methods along with sampling techniques by applying criteria that are in accordance with the purpose of research, namely purposive sampling, grounded in the Theory of Planned Behavior (TPB) and Compliance Theory. Primary data were obtained from 99 registered taxpayers via a structured questionnaire and subsequently analyzed through multiple linear regression using IBM SPSS version 26. The findings demonstrate that the tax amnesty program, taxpayer awareness, tax understanding, and service quality each have a positive and significant effect on taxpayer compliance, while the transfer fee exemption has a negative and significant effect. The overall model explains an adjusted R2 of 72.5% of the variance in taxpayer compliance. These results indicate that long-term compliance is influenced more by cognitive and institutional factors than by short-term fiscal incentives. This study extends existing literature by combining tax policy instruments with behavioral determinants within the framework of the Theory of Planned Behavior, specifically in the context of regional taxation.